Electronic and optical investigations of Be2C monolayer: Under stress and strain conditions. (April 2017) - Naseri, Mosayeb; Jalilian, Jaafar
Abstract : Graphical abstract: Abstract : Highlights: The electronic and optical properties of Be2 C monolayer under stress and strain are investigated. Be2 C monolayer is a direct band gap semiconductor. By exerting stress, the energy band gap of the compound is reduced while the energy gap is increased when a strain is applied. The direct band gap of Be2 C monolayer turns indirect when biaxial strains are applied. The optical calculations indicate the transparency of Be2 C monolayer in low energy range. Abstract: A Be2 C monolayer, as a new direct band gap semiconductor, has good potential for use in optoelectronic applications. In this article, the effects of different biaxial stresses and strains on the electronic and optical properties of a Be2 C monolayer are investigated via first-principles calculations in the frame work of the density functional theory. The study of the electronic properties indicates that under biaxial strains, the direct band gap of the Be2 C monolayer becomes indirect ( K → Γ ), while under stress, it remains direct. In addition, the energy gap increases under strain, while it decreases under stress conditions. The optical calculations show that strain and stress effects cause red and blue shifts, respectively, in the optical spectra. Furthermore, the low values of reflectivity and absorption in the low energy ranges indicate the transparency of this monolayer. These results can be used in the fabrication of future nanoelectronic systems.